Exploring first‐time mothers' experiences and knowledge about behavioural risk factors for stillbirth - Tamara Escañuela Sánchez; Karen Matvienko‐Sikar; Sarah Meaney; Keelin O'Donoghue (Wiley, 2023)
Abstract Background Modifiable factors such as substance use, lack of attendance at antenatal care, overweight or obesity and sleeping position are associated with a higher risk of stillbirth. This qualitative study aimed to explore women's experiences of modifiable factors during pregnancy and their awareness of stillbirth. Methods Purposive sampling was implemented by hospital staff in a large tertiary maternity hospital in Ireland between November 2020 and March 2021. Women were approached during their stay in the hospital and were invited to participate in a semistructured interview 3-5 months later. Eligible women were primiparous, >18 years of age and had an uncomplicated pregnancy and delivery. Eighteen women who consented to be followed up were interviewed at 3-5 months postpartum. Thematic analysis was used to analyse the data. Results Four themes were identified: attitudes towards behaviour change, awareness regarding stillbirth and risk factors, the silence around stillbirth and risks, and attitudes towards receiving information about stillbirth. Women spoke about behaviour change in terms of outcomes, and most changes (e.g., ceasing alcohol consumption) were perceived as easy to manage. Awareness of stillbirth was limited among the women interviewed, and the association between risk behaviours and stillbirth was not known by any woman. Results suggest that there is a silence around stillbirth, including in antenatal care, which hinders information provision. However, most women highlighted the value of receiving information and extra education about modifiable risk factors and stillbirth. Conclusion There is a general lack of understanding of the link between behavioural risk factors and potential pregnancy outcomes such as stillbirth. Providing further information to women about stillbirth and providing additional support with behaviour change might contribute to enhancing preventive efforts. Patient or Public Contribution Patients were involved in this study by providing their experiences of antenatal care which were used as primary data.